The neural correlates of sex differences in emotional reactivity and emotion regulation - Domes, Gregor; Schulze, Lars; Böttger, Moritz; Grossmann, Annette; Hauenstein, Karlheinz; Wirtz, Petra H.; Heinrichs, Markus; Herpertz, Sabine (Human brain mapping, 2010)
Sex differences in emotional responding have been repeatedly postulated but less consistently shown in empirical studies. Because emotional reactions are modulated by cognitive appraisal, sex differences in emotional responding might depend on differences in emotion regulation. In this study, we investigated sex differences in emotional reactivity and emotion regulation using a delayed cognitive reappraisal paradigm and measured whole-brain BOLD signal in 17 men and 16 women. During fMRI, participants were instructed to increase, decrease, or maintain their emotional reactions evoked by negative pictures in terms of cognitive reappraisal. We analyzed BOLD responses to aversive compared to neutral pictures in the initial viewing phase and the effect of cognitive reappraisal in the subsequent regulation phase. Women showed enhanced amygdala responding to aversive stimuli in the initial viewing phase, together with increased activity in small clusters within the prefrontal cortex and the temporal cortex. During cognitively decreasing emotional reactions, women recruited parts of the orbitofrontal cortex, the anterior cingulate, and the dorsolateral prefrontal cortex to a lesser extent than men, while there was no sex effect on amygdala activity. In contrast, compared to women, men showed an increased recruitment of regulatory cortical areas during cognitively increasing initial emotional reactions, which was associated with an increase in amygdala activity. Clinical implications of these findings are discussed.